The analysis of Lithuanian men's national handball team in the qualification of the XVIII World Championship - Skarbalius, A.; Strielciunas, R.; Purvys, D. (Education. Physical training. Sport, 2004)
The registration and analysis of competition activities let us foresee the tendencies of sports trends, predict sports results, foreknow the trends of the preparation of athletes (Lees, 1999; Reilly, 1993; Skarbalius 2000, 2001). The aim of the research is to establish the peculiarities of the performance of Lithuanian Men`s Handball National Team (LTU) in the qualification of World Championship XVIII. In 2002 six qualification matches of World Championship XVIII with the teams of Belorussia, Bulgaria and Latvia were observed. Team activities were analysed using the computer programmes (Skarbalius, Strielèiunas, 1999). The methods of mathematical statistics (mean ± SD, variation coefficient, reliability of meaning differences determined by Student criterion t (significance level p < 0.05)) were used to determine the differences between the indicators of playing peculiarities of the elite national teams and the former playing of Lithuanian National Team. LTU was most successful (65.2 ± 6.1%) applying the defence system 5:1. LTU defended against positional attacks 44.6 ± 4.3 times with the efficiency of 66.9 ± 5.3% during a match on average. While the opponents played effectlessly at 6—9 metre zone, LTU deffensive efficiency was 70.9 ± 6.9%, and even 82% in the match against the Bulgarian national team. However, LTU deffensive efficiency was low when the opponents were active at 6—9 metre zone — 35.5 ± 30%. LTU defence was best against individual counterattacks — 54.2 ± 51%, a little worse against team counterattacks — 32.9 ± 38.2% and the worst against group counterattacks — 26.2 ± 29.5%. The highest efficiency of LTU in defence was when the number of players was equal — 69.1 ± 5.4%, lower with the numerical superiority (61,9 ± 34,5%) and the lowest efficiency was playing with the numerical minority (57.4 ± 14.8%). LTU defended most effectively (80.7 ± 13.2%) when the attacks lasted 45—60 seconds, and least effectively when the attacks lasted up to 20 seconds (63.9 ± 19.5%) and between 30—45 seconds (62.9 ± 11.3%). In offence LTU attacked 54.8 ± 4.3 times during a match on average with the attack efficiency of 49.1 ± 6.9%. In the positional way LTU attacked 43.3 ± 2.7 times with the efficiency of 45.5 ± 6.1%. In World Championshipstatistically reliably (p < 0.05) 4.9 attacks fewer than the national tems at the Sydney Olympic Games on average (59.7 ± 4.3). Though LTU plays faster and faster, it still lags behind elite combined teams. In World Championship XVIII LTU attacked as effectively as in European Championship V (49 ± 4.1%), and statistically reliably (p < 0.05) 7.2% more effectively than the national teams at the Sydney Olympic Games (41.9 ± 6.7%). At present LTU plays slower, but more rationally than elite teams. LTU was more successful at overcoming the defensive system 5:1 (53.1 ± 28.9%) than 6:0 (35.1 ± 20.9%). In this championship LTU attacked 4.8% worse when they actively played in 6—9 metre zone, and a little worse (1.6%) when they inactively played at 6—9 metre zone than in European Championship V (65.2 ± 11.9 and 38.6 ± 8.6% respectively). In this way LTU enlarged its possibilities to attack goal in other ways as well, but it lost the features of active playing. Most effectively LTU finished its counterattacks in a team way (80 ± 29.8%), less effectively — individual counterattacks (69.3 ± 32.5%) and least effectively — group counterattacks (56.9 ± 17.2%). Though World Championship XVIII LTU was 3% better in counterattacks than in European Championship V (55.8 ± 10.8%), it was 20.1% worse (statistical reliability p < 0.05) than the elite national teams at the Sydney Olympic Games (75.9 ± 7.3%). The quality of playing of LTU is significantly worse than of elite national teams. LTU played most successfully with the numerical superiority of players (46.4 ± 6.5%), and less successfully with the equal number of players (45 ± 11.4%). This tendency proves the lack of players` communication skills. LTU offence was most effective when the attacks lasted 30—60 seconds. The lower efficiency of attacks when they lasted 20 seconds, compared to the European Championship V, should be considered as a negative tendency. XVIII LTU attacked faster by three attacks than in European Championship V (51.8 ± 2.8), but